2020
DOI: 10.1038/s41467-020-15084-4
|View full text |Cite
|
Sign up to set email alerts
|

Histone variant H3.3 residue S31 is essential for Xenopus gastrulation regardless of the deposition pathway

Abstract: Vertebrates exhibit specific requirements for replicative H3 and non-replicative H3.3 variants during development. To disentangle whether this involves distinct modes of deposition or unique functions once incorporated into chromatin, we combined studies in Xenopus early development with chromatin assays. Here we investigate the extent to which H3.3 mutated at residues that differ from H3.2 rescue developmental defects caused by H3.3 depletion. Regardless of the deposition pathway, only variants at residue 31-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 108 publications
(142 reference statements)
0
39
0
Order By: Relevance
“…H3.3 only differs from H3.2 by four residues: Ser31 in the tail, and three substitutions within the core of H3 which dictate chaperone selectivity ( Ahmad and Henikoff, 2002 ; Elsässer et al, 2012 ; Liu et al, 2012 ). Phosphorylation of Ser31 in H3.3 is important for regulation of cell fate during gastrulation and for enhancer activation ( Martire et al, 2019 ; Sitbon et al, 2020 ) and Ser31P influences H3.3 K27 trimethylation and acetylation ( Martire et al, 2019 ; Sitbon et al, 2020 ), and so phosphoregulation via S31 may provide an additional mechanistic link as to why the Gly 34 mutations are only found in H3.3.…”
Section: Discussionmentioning
confidence: 99%
“…H3.3 only differs from H3.2 by four residues: Ser31 in the tail, and three substitutions within the core of H3 which dictate chaperone selectivity ( Ahmad and Henikoff, 2002 ; Elsässer et al, 2012 ; Liu et al, 2012 ). Phosphorylation of Ser31 in H3.3 is important for regulation of cell fate during gastrulation and for enhancer activation ( Martire et al, 2019 ; Sitbon et al, 2020 ) and Ser31P influences H3.3 K27 trimethylation and acetylation ( Martire et al, 2019 ; Sitbon et al, 2020 ), and so phosphoregulation via S31 may provide an additional mechanistic link as to why the Gly 34 mutations are only found in H3.3.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from two laboratories recently showed that H3.3S31ph stimulates the catalytic activity of histone acetyltransferase p300, thus maintaining enhancers at an open, acetylated chromatin state permissive to the embryonic development program. 4,5 In the current study, Armache et al 2 discovered a novel role of H3.3S31ph in transcription elongation. It not only augments the catalytic activity of SETD2, but also ejects negative regulator ZMYND11.…”
Section: H33s31 Phosphorylation: Linking Transcription Elongation Tomentioning
confidence: 56%
“…Several recent studies also demonstrate a link between H3.3 phosphorylation and p300 activity at enhancers [ 57 , 164 ]. Interestingly, the N-terminal tails of canonical H3 and H3.3 differ by only one amino acid.…”
Section: Mechanisms Of Cbp/p300 Activationmentioning
confidence: 94%
“…While H3.1 and H3.2 contain an alanine at position 31, H3.3 has a unique and highly conserved serine that has been reported to be phosphorylated by both checkpoint kinase 1 (Chk1) and Aurora B [165][166][167]. A study from the Almouzni lab demonstrates that a phosphomimetic mutant of H3.3 at this position (H3.3S31D) results in increased H3K27ac in cis in both human cell lines and Xenopus embryos [164]. Our own work demonstrates that phosphorylation of H3.3 Ser31 (H3.3S31ph) facilitates p300 activity not only on phosphorylated tails, but also in trans on canonical H3 substrates in mESCs (figure 2b) [57].…”
Section: Mechanisms Of Cbp/p300 Activationmentioning
confidence: 99%